2006
DOI: 10.1136/jnnp.2005.067777
|View full text |Cite
|
Sign up to set email alerts
|

Variability of antiepileptic medication taking behaviour in sudden unexplained death in epilepsy: hair analysis at autopsy

Abstract: Background: Variable compliance with antiepileptic drugs (AEDs) is a potentially preventable cause of sudden unexplained death in epilepsy (SUDEP). Hair AED concentrations provide a retrospective insight into AED intake variability. Methods: We compared hair AED concentration variability in patients with SUDEP (n = 16), non-SUDEP epilepsy related deaths (n = 9), epilepsy outpatients (n = 31), and epilepsy inpatients (n = 38). AED concentrations were measured in 1 cm hair segments using high performance liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 13 publications
0
17
0
1
Order By: Relevance
“…In a recent study, post-mortem hair AED concentrations demonstrated that observed variability in AED-taking behavior was significantly greater in patients who had died from SUDEP compared with epilepsy outpatients or inpatients [59]. The most likely explanation was greater variability in AED ingestion among SUDEP patients.…”
Section: Compliancementioning
confidence: 98%
“…In a recent study, post-mortem hair AED concentrations demonstrated that observed variability in AED-taking behavior was significantly greater in patients who had died from SUDEP compared with epilepsy outpatients or inpatients [59]. The most likely explanation was greater variability in AED ingestion among SUDEP patients.…”
Section: Compliancementioning
confidence: 98%
“…53 Directly asking patients if they take their prescribed medication regularly, in a nonjudgmental and sympathetic way, might reveal that compliance is poor, even without blood testing; assaying drug levels in hair can give a longer-term record of compliance. 54 In the management of any epilepsy, and refractory epilepsies in particular, it is always worth ensuring, from a clinical perspective, that 'trivial' causes of apparent refractoriness have been excluded. For example, at specialist centers, a significant proportion (~20%) of patients who are evaluated for apparently refractory epilepsy turn out not to have epilepsy at all.…”
Section: Current Management Of Refractory Epilepsy Investigationsmentioning
confidence: 99%
“…These patients are exposed to a higher risk of seizures and an increased time to remission [4]. Low adherence to AEDs may also be associated with increased mortality including sudden unexplained death [5], and hospital admissions [6]. Whilst large crosssectional studies have demonstrated substantial difference in health outcomes between patients with high and low adherence, prospective studies are lacking.…”
Section: Introductionmentioning
confidence: 99%